Tsarist responses to the Armenian question in the South Caucasus between 1878 and 1903 - Akgul, Mehmet (2024)
From the Tsarist assault on the Armenian parish schools in the beginning of the 1880s to the confiscation of the Armenian Church properties in 1903, the affairs between the Russian Empire and its Armenian subjects gradually deteriorated. The amicable bond and religious solidarity that portrayed the relationship between the Russians and Armenians until the last quarter of the nineteenth century faded in the age of nationalism. Ethnicity and politics rather than religion became a key defining factor in the Russian imperial encounter with its Armenian subjects in this period. The aim of this dissertation is to scrutinize this Russian imperial encounter with its Armenian subjects between these years. It argues that the Russian authorities reacted rather than acted against this perceived danger of Armenian nationalism and the growing Armenian Question in the South Caucasus as well as across the border in the Ottoman Empire. Instead of presenting a traditional enumeration of repressions, this dissertation aims to provide a balanced historical examination of this complex interplay between the Russian authorities and its Armenian subjects in the age of nationalism. On one hand, the Russian authorities were searching the new ways and methods of maintaining the imperial unity and integration of its subjects into imperial order. On other hand, the Armenian religious and secular forces; i.e. the Armenian Church authorities and Armenian political parties, were endeavoring to determine their own future in a concerted action with their ethnic brethren across the borders in the Ottoman Empire. The Tsarist assault on Armenian parish schools in 1884 to curb the indoctrination of breeding nationalist ideas flourishing among the Armenians at home and abroad turned into an uncompromising antagonism between the Russian authorities and Armenian Church leadership as well as Armenian political parties in the later decade. By 1903, this deterioration reached its apex with the confiscation of the Armenian Church properties following the implementation of a series of policies to cripple the demographic, economic and political influence of its Armenian subjects in the South Caucasus.